Methods of the terrain allowable slope determining for safe operation of specialized equipment under the non-stationary load action - Machuga, Oleg; Borys, Mykola; Lusta, Yurii (Mechanics and Advanced Technologies, 2022)
The operation of modern high-tech equipment requires a clear delineation of safe conditions for its operation. To a large extent, this applies to machines that move and work on untreated soil surface: forestry machinery, agricultural machinery, road construction machinery, military equipment, and so on. Asymmetry of the location of the working bodies, work on surfaces with a lateral slope, non-stationary interaction with the working environment - these are the factors that increase operational risks. Objective of this study is to establish the limits of safe operation of specialized machines operating on a rough surface with a slope to the horizon. The methods of determining safe slopes for the above-described equipment in the conditions of its non-stationary interaction with the subject of work are considered in the work. In particular, dangerous slopes that can cause the car to overturn or roll sideways are identified. The realization of this goal is achieved by building a mathematical model and appropriate calculation schemes that cover both possibilities of loss of stability. Graphs are plotted to display the maximum slopes due to the overturning and sliding of the machine on the slope for the specified operating loads. The integral characteristic of the slope limit value covers both of the above risks. The application of the proposed methods is illustrated by the calculation of the safe slope for firing tanks for different angles of deviation of the gun from the surface of the movement on the slope and the type of ground surface of the movement. The following results were obtained: methods for calculating the allowable slopes for the possibility of operating specialized machines on them, taking into account soil conditions, and demonstrated the application of the approach to the case of military equipment. The use of these results is a necessary factor for the implementation in the design of technological processes for specialized machines in order to minimize operational risks.